SAT0101 Abatacept Treatment Suppresses T Cell Activation in Anti-Cyclic Citrullinated Peptide Antibody (ACPA) Positive RA Patients but not in Acpa Negative RA Patients. (23rd January 2014) - Matsutani, T.; Murakami, M.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Namiki, M.; Ohmura, K.; Imura, Y.; Fujii, T.; Kuroiwa, T.; Nakahara, H.; Hika, S.; et al.
Abstract : Background: We have reported that abatacept (ABA) treatment suppressed T cell activation and reduced plasma levels of interleukin (IL)-6 in rheumatoid arthritis (RA) patients. Anti-cyclic citrullinated peptide antibodies (ACPA) are highly specific and sensitive marker for RA. Production of autoantibody such as ACPA depends largely on an interaction between CD4+ helper T cells and antibody-producing B cells. Objectives: The aim of this study is to elucidate different effect of ABA on T cell activation, T cell subsets and cytokine profiles between ACPA+ an ACPA− patients with RA. Methods: PBMCs and plasmas were collected from healthy individuals (n=15) and RA patients (n=45) enrolled in abatacept research outcome as a first-line biological agent in the real world (ABROAD study) at baseline and 24 weeks after ABA treatment. Surface phenotypes and activation markers of T cells were analyzed with FACS. Treg cells (CD4+CD25+Foxp3+) were measured with intracellular staining with anti-Foxp3 antibody. After in vitro stimulation with PMA/Ionomycin, cells were intracellularly stained with anti-IFN-γ, anti-IL-4 or anti-IL-17A antibodies. ACPA titers were determined with EliA™ CCP ELISA kit. Results: At baseline, there were no significant differences in CRP, DAS28-CRP, MMP-3 between ACPA+ (>4.5U/mL, n=38) and ACPA− RA patients (n=7). Remission rate (DAS28-CRP<2.3) at 24 weeks was 43% (16/38) in ACPA+ and 14% (1/7) in ACPA− patients, respectively. Changes of DAS28-CRP during 24 weeks of ABA treatment were greater in ACPA+ (2.0±1.1) than in ACPA− patients (1.3±0.66). Proportion of CD25+ in CD4+ T cells was higher in ACPA+ than in ACPA− patients at baseline and significantly decreased in ACPA+ (11.1±5.6% → 5.5±5.0%, P <0.001) but not in ACPA− patients (5.9±2.9% → 4.4±3.0%) after ABA treatment. The proportions of Treg, Th2 and Th17 cells significantly decreased in only ACPA+ patients. Conclusions: CD4+ T cells were more activated in ACPA+ patients who responded well to ABA treatment than in ACPA− patients. ABA treatment reduced activated CD4+CD25+ T cells in ACPA+ patients but not in ACPA− patients. It is suggested that ABA has more effective on ACPA+ patients by suppressing T cell activation. Disclosure of Interest: T. Matsutani Speakers bureau: Bristol-Myers Squibb Japan, M. Murakami: None Declared, M. Sekiguchi Grant/research support from: Bristol-Myers Squibb Japan, Speakers bureau: Bristol-Myers Squibb Japan, K. Matsui Grant/research support from: Bristol-Myers Squibb Japan, M. Kitano Grant/research support from: Bristol-Myers Squibb Japan, M. Namiki Grant/research support from: Bristol-Myers Squibb Japan, K. Ohmura Grant/research support from: Bristol-Myers Squibb Japan, Y. Imura Grant/research support from: Bristol-Myers Squibb Japan, T. Fujii Grant/research support from: Bristol-Myers Squibb Japan, T. Kuroiwa: None Declared, H. Nakahara: None Declared, S. Hika: None Declared, K. Maeda: None Declared, Y. Nozaki Grant/research support from: Bristol-Myers Squibb Japan, M. Funauchi Grant/research support from: Bristol-Myers Squibb Japan, K. Murakami: None Declared, T. Ikawa: None Declared, S. Irimajiri: None Declared, A. Nampei: None Declared, T. Azuma: None Declared, T. Sasaki: None Declared, A. Yokota: None Declared, S. Morita: None Declared, Y. Kawahito Grant/research support from: Bristol-Myers Squibb Japan, T. Mimori Grant/research support from: Bristol-Myers Squibb Japan, H. Sano Grant/research support from: Bristol-Myers Squibb Japan, N. Nishimoto Grant/research support from: Bristol-Myers Squibb Japan